Polarization‐independent multiband metamaterials absorber by fundamental cavity mode of multilayer microstructure - Fang, Bo; Li, Boya; Peng, Yandong; Li, Chenxia; Hong, Zhi; Jing, Xufeng (Microwave and optical technology letters, 2019)
We propose a multiband metamaterial absorber consisting of silicon brick array on metal substrate in infrared range. Using the regular hexagon array of silicon bricks, the absorption rate can reach to 90% over the bandwidth of 100 nm, and four absorption peaks with the absorption rate of more than 98% can be obtained. The absorber is independent on polarization angle. The multiband absorption performance can be attributed to primary cavity mode and Mie resonance in silicon bricks. Importantly, when the all‐dielectric silicon bricks are replaced by metal‐dielectric‐metal sandwich structure, the absorption rate above 75% with the bandwidth of more than 200 nm in the absorber can be realized, and it is polarization‐insensitive. The absorption peaks are increased to obtain broadband absorption. Our designed sandwich microstructure can generate the resonance effect of magnetic dipole among coupled layers, leading to the characteristics of broadband absorption.